PEMBENTUKAN KATA DALAM BAHASA CIA-CIA BUTON, SULAWESI TENGGARA - Ramla Ramla; Umi Hartati (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aims to describe the formation of words in Cia-cia language which consists of (1) affixation in Cia-cia, (2) reduplication in Cia-cia, (3) composition in Cia-cia. This research includes descriptive qualitative research type. This research data in the form of sentences in Cia-cia language in which there is a word that has experienced morphological process. The data source of this research is all sentence result of libat ably containing word formation in Cia-cia used by student of Buton, Southeast Sulawesi. Methods and techniques used in data collection is a method of referring to tapping techniques, techniques libat skillful conversation, and the technique of record. Data analysis method used is the method of agih and referential reference method. Method of presentation of result of data analysis in this research is done by using informal method. The result of this research is the formation of words in Cia-cia language consisting of (1) Affixation in Cia-cia language there are four kinds, that is prefixation, infixasi, suffix, and confixasi. The prefixes in the Cia-cia language are of four kinds, namely ci- in Indonesian means di- and ter-, po- means ber, and meN-, pi- means ber and meN- while ka- means peN- and meN -. Infix there is only one, that is -ko-. There are three kinds of suffixes, namely -e means -kan, - po b means -, and –no means - them. There are two kinds of confixes pa-sie / meng-kandan ka-ya / beran. (2) Reduplication there are three kinds, namely overall reduplication, partial reduplication, and reduplication with phoneme changes. (3) The composition consists of nouns and nouns, nouns and verbs, and nouns and adjectives.